Impact of Different Tax Variables on The Economic Growth of Nepal - Vasishtha, Veetihotra (Journal of Nepalese Management and Research, 2023)
This study examines the impact of different tax variables on GDP growth. Timeseries secondary data were gathered from the Economic Survey issued across several fiscal years to meet the study’s objectives. The acquired data was analyzed using the log-linear regression model. The research hypotheses were tested using SPSS 20 software. The regression model included independent variables (tax) and the dependent variable GDP. The findings show that direct tax has an adverse association with GDP, whereas indirect tax has a positive link. Notably, overall revenue has a significant beneficial impact on GDP. Despite positive trends in tax revenue, they need to meet the government expenditure in Nepal. Across all regression models, the R2 coefficient exceeds 95%, indicating a high degree of determination among variables.